The Influence of Family Support According to Gender in the Portuguese Language Course Achievement - Pires, Heldemerina S.; Candeias, Adelinda A.; Grácio, Luísa; Galindo, Edgar; Melo, Madalena (Frontiers in Psychology, 2017)
Several factors like pupils’ characteristics, school conditions and family context have been pointed out in the literature as being linked to academic achievement. Regarding the latter, family socio-economic status and parental support have been identified as determining variables on success at school. The current study analyses the influence of family support on the achievement of school children in their native language (Portuguese Language Course (PLC)). Participants were 885 students attending PLC on basic and secondary schools (6th and 9th school grades) (ISCED 1); 418 boys and 467 girls, ranged between 10 and 18 years of age (M=12.99). School achievement was assessed using year-end classifications in PLC. Family support was assessed using the Family Support-Context Variables Questionnaire. A regression analysis showed that students’ perception about instrumental and affective family support in school life was positively related to their Portuguese grades. However, different predictive values were revealed according to gender. Girls’ Portuguese languge couse classification seemed to depend on affective variables like their perception of affective parental support and affective attitudes towards the Portuguese language course, while boys´ results seemed to be influenced by instrumental variables, such as the perception of instrumental support from parents and boys’ attitudes toward the utility of learning Portuguese language. These results supported those of other studies, showing the need to take gender differences into account in educational interventions, especially during early adolescence. In conclusion, the study shows an influence of parental support on PLC achievement. Such influence differs according to gender, with girls being more sensitive to the affective dimension of parental support and boys to the instrumental one.